PERTANGGUNGJAWABAN PIDANA PIHAK LEASING YANG MEMPEKERJAKAN DEBT COLLECTOR DALAM MENYELESAIKAN PIUTANG DENGAN MELAKUKAN PENGANIAYAAN DI KEPOLISIAN RESORT KOTA PEKANBARU - Habib, Ikhwan; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Some actions of debt collectors even lead to criminal action. For example, debt collectors who act forcibly seized goods, making a scene, terrorizing either directly or phone, even threatened to kill customers and that just happened, killed his case Uniting Nations Party Secretary "Irzen Octa" Citi bank customers some time ago makes this profession become the subject of society. A number of the ins and outs of this profession continues to be discussed, ranging from the authority, the power even to the effect on public confidence related to banks using their services.To exert this study, the authors make the research questions are: criminal liability leasing party debt collectors are employed in finish receivables with maltreatment and criminal liability debt collector who completed receivables with maltreatment in Pekanbaru City Police.Terms of the method used, this research can be classified in socio-juridical type of research is secondary data, to then proceed with the study of primary data in the field, or in accordance with the fact that life in society. the nature of the research can be classified as descriptive research, because in this study the authors conducted research directly on location or places studied aiming to obtain a clear and complete picture about a situation or problem under studyThe Criminal Liability The Hiring Leasing Debt Collector. In Resolving receivable by Doing persecution, including elements of fault liability (Schuld) due to the need for an error can be imprisoned, it is in line with the principle in criminal law that can not be convicted if there is no error, while the error is not a corner of the normative sense. Forcibly confiscated goods and commit the crime of persecution by the debt collector is a violation of law, the action it can indicate criminal offense of theft (Article 362 of the Criminal Code) to take the goods which partly or wholly owned by others unlawfully. For violations of the law, motorcycle buyers are entitled to report it to the police.Keyword: Responsibility, Debt Collector, Persecution